UTILIZATION OF WAYGROUND AS AN EVALUATION MEDIA FOR LEARNING ANECDOTE TEXTS: A MIXED METHODS STUDY ON GRADE X HIGH SCHOOL STUDENTS - ahmad reza dliyaullah; Fina Zaidatul Istiqomah (JURNAL KONFIKS, 2026)
Evaluation of Indonesian language learning in anecdotal text material is still dominated by conventional methods that tend to be oriented towards the final results and less actively involve students in the learning process. This condition encourages the need to utilize digital technology as a more interactive and effective evaluation tool. This study aims to analyze the differences in student learning evaluation results between the use of Wayground and conventional evaluation and describe student and teacher responses to the use of Wayground in learning anecdotal text. The study used a mixed methods approach with an embedded mixed methods design. The research subjects consisted of 20 students of class X.2 SMAN 1 Cluring who were divided into a Wayground group (10 students) and a conventional group (10 students). Data were collected through learning outcome tests, observations and semi-structured interviews. Quantitative data were analyzed using descriptive statistics and Independent Samples t-Test, while qualitative data were analyzed using the Miles and Huberman model. The results showed that the average score of the Wayground group (86.5) was higher than the conventional group (81.0). However, the results of statistical tests showed that the difference was not significant (t = 1.169; p = 0.258). Qualitative findings indicate that Wayground increased student engagement, enthusiasm, independence, and participation during the evaluation. Teachers assessed that Wayground streamlined the assessment process, expedited the delivery of evaluation results, and supported the provision of direct feedback. Students also found the evaluations more engaging and facilitated understanding of the material. Despite challenges such as limited internet connection and devices, Wayground has the potential to support more interactive, efficient, and student-centered learning evaluations.